Genetic Predisposition for Dermal Problems in Hexavalent Chromium Exposed Population. (26th July 2012) - Sharma, Priti; Bihari, Vipin; Agarwal, Sudhir K.; Goel, Sudhir K.
Abstract : We studied the effect of genetic susceptibility on hexavalent chromium induced dermal adversities. The health status of population was examined from the areas of Kanpur (India) having the elevated hexavalent chromium levels in groundwater. Blood samples were collected for DNA isolation to conduct polymorphic determination of genes, namely: NQO1 (C609T), hOGG1 (C1245G), GSTT1, and GSTM1 (deletion). Symptomatic exposed subjects ( n = 38 ) were compared with asymptomatic exposed subjects ( n = 108 ) along with asymptomatic controls ( n = 148 ) from a non contaminated reference community. Exposed symptomatic group consisted of 36.8% subjects who were GSTM1 null genotyped as compared to asymptomatic where only 19.4% subjects were null. The exposed subjects with GSTM1 null genotype were more susceptible to dermal adversities in comparison with wild genotyped subjects (OR = 2.42; 95% CI = 1.071–5.451). Age, smoking, gender or duration of residence were not found to have any confounding effect towards this association. Association with other genes was not statistically significant, nonetheless, possible contribution by these genes cannot be ruled out. In conclusion, variation in the polymorphic status of GSTM1 gene may influence dermal outcomes among residents from Cr(VI) contaminated areas. Further studies are therefore, needed to examine these observations among different population groups.